1996
DOI: 10.1021/cm950417h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hybrid Organic−Inorganic Materials from Interpenetrating Polymer Network Chemistry

Abstract: Organic−inorganic interpenetrating polymer networks were synthesized with an SiO2 phase made by sol−gel chemistry and the organic phase made from poly(2-hydroxyethyl acrylate). The resultant morphologies were characterized by small-angle scattering and electron microscopy. When the vinyl polymerization is more rapid than the sol−gel reaction, gross phase separation occurs giving a heterogeneous structure. For comparable rates of the two polymerizations, the specimens have a dendritic morphology on the scale of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 28 publications
3
79
0
Order By: Relevance
“…The sol-gel process is a useful synthetic method for the preparation of amorphous, as well as structurally ordered, materials. It offers advantages such as the possibility of obtaining homogeneous hybrid materials at low temperature, thereby enabling the incorporation of a variety of compounds [28][29][30][31][32][33][34]. A typical sol-gel method is based on hydrolysis and condensation of the precursor (inorganic metal salts or metal organic compounds such as metal alkoxides) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel process is a useful synthetic method for the preparation of amorphous, as well as structurally ordered, materials. It offers advantages such as the possibility of obtaining homogeneous hybrid materials at low temperature, thereby enabling the incorporation of a variety of compounds [28][29][30][31][32][33][34]. A typical sol-gel method is based on hydrolysis and condensation of the precursor (inorganic metal salts or metal organic compounds such as metal alkoxides) [24].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Jackson et al [113] observed phase separation when the free radical polymerization of the acrylate groups was fast with respect to the sol-gel reaction. Rodríguez et al [149] also observed a highly efficient filling of the silica pores by the organic polymer matrix' chains in PHEA/SiO 2 nanocomposites obtained by a similar procedure, and related it with the silica polymerization occurring faster than the organic polymerization.…”
Section: Compression Testmentioning
confidence: 94%
“…Polymers that have been hybridized with this purpose include poly(ε-caprolactone) [103][104][105][106] , poly(2-hydroxyethyl methacrylate) [89][90][91][107][108][109][110][111][112] , poly(2-hydroxyethyl acrylate) [113] , poly(methyl methacrylate) [92,114] , poly(butyl acrylate) [115] , poly(ethylene oxide) [116,117] , poly(ethylene oxide-co-epichlorhydrin) [118] , polyimide [119] , polyamide 6,6 [120] , poly(vinyl acetate) [121] , or poly(vinyl alcohol) [122] .…”
Section: Polymer/silica Nanohybrids Obtained By Sol-gel Processmentioning
confidence: 99%
See 2 more Smart Citations